EFEK KUALITAS KONTRUKSI, PELAYANAN, DAN HARGA TERHADAP VOLUME PENJUALAN RUMAH - Romagia SE.,M.Si; Reza Safitri (STIA Indragiri, 2016)
ABSTRACT This study aimed to analyze the determination of building construction, service and price on volume of house sales. This study uses three independent variables construction, service and price, with one dependent variable namely sales volume. The use of variables in this study is expected to determine how the process is going on and what are the factors driving the creation of a good sales volume in PT. Adi bintan Permata Batam. Samples were the buyers of the house in Citra Permata Residence 154 people. Samples were taken by sampling techniques. Data analysis method used is quantitative analysis, the validity, reliability test, classic assumption test, multicoloniarity test, heteroscedasticity test, normality test, multiple linear regression analysis, t-test, f-test the coefficient of determination R2. Based on the results of data analysis showed that: the variable construction has a significant influence on the performance of the test value t sig of 0.068 > 0.05, service variables have significant effects on sales volume with a value of 0.179 t test sig > 0.05 price variable also has a significant influence on the performance of the test value t sig of 0.000 < 0.05. Based on calculations Test f, together variable construction, service, and price have a significant effect on sales volume with the value of F sig 0.000 < 0.05.Keywords: Construction, Service, Price, Sales Volume